FACTORS ASSOCIATED WITH ORAL CANCER RISK BEHAVIORS AMONG THE SENIOR CITIZENS IN UBON RATCHATHANI PROVINCE - Huaisai, Wuttichan; Kanking, Kewalin; Chaiyabut, Nitchaphat; Somhom, Wanpen (Primary Health Care Journal (Northeastern Edition), 2025)
Oral cancer is a type of malignancy that occurs in the mucosal tissues of the oral cavity. It is commonly found among older adults and has significant impacts on their quality of life, particularly in terms of physical appearance, speech, voice, and swallowing. Personal health behaviors are considered a critical factor influencing the development of oral cancer. This cross-sectional descriptive study aimed to examine risk behaviors associated with oral cancer and related factors among older adults in Ubon Ratchathani Province. A total of 419 participants were selected using multi-stage random sampling. Data was collected through questionnaires and analyzed using descriptive statistics, Fisher’s exact test, and Spearman’s rank correlation coefficient. The findings revealed that most participants exhibited low levels of risk behaviors for oral cancer (97.14%). According to the Health Belief Model, 64.20% and 58.71% of participants had high levels of perceived benefits of disease prevention and perceived severity of the disease, respectively. Meanwhile, 91.89% and 66.35% had moderate levels of perceived barriers to prevention/treatment and perceived susceptibility to the disease, respectively. Significant correlations were found between oral cancer risk behaviors and perceived susceptibility (rs = –0.198, p < 0.001) as well as perceived barriers (rs = 0.159, p = 0.001). In conclusion, older adults with greater awareness of disease susceptibility tend to engage in fewer risk behaviors, whereas those perceiving more barriers are more likely to engage in risky behaviors. Public health agencies should incorporate the Health Belief Model into primary-level oral health promotion policies, with a focus on increasing risk perception and reducing access barriers to effectively prevent and reduce oral cancer risk behaviors among the elderly.